Reconciliation of scrum and the project management process of the ISO/IEC 29110 standard-Entry profile—an experimental evaluation through usability measures - Galvan-Cruz, Sergio; Mora, Manuel; Laporte, Claude Y.; Duran-Limon, Hector (Software quality journal, 2021)
Software process standards and models are used in large- and medium-sized organizations to reach the Iron Triangle . In contrast, small and very small entities either ignore them or cannot apply them because these standards and models are technically and economically not affordable. Consequently, agile software development practices are usually used by small and very small organizations. The ISO/IEC 29110 series of standards and guides are now available for very small organizations, but their utilization with agile practices represents an agility-rigor reconciliation problem. In this research, we report the experimental evaluation of Scrum + EPG (a reconciled agile-rigorous software Project Management process from Scrum, and the Project Management process of the ISO/IEC 29110 series-Entry profile, documented in an Electronic Process Guide). Scrum + EPG was compared to Scrum EPG (a non-modified Scrum process also documented in an Electronic Process Guide). Thirty-two international academicians and practitioners, including experts and novices on agile practices, from Latin America, North America, and Asia–Pacific regions, evaluated six metrics of usability. A within-subjects design and Wilcoxon matched-pairs signed-rank tests were applied for collecting and analyzing the experimental data. The statistical results support the claim that the Scrum + EPG was considered a high-quality conciliated agile-rigorous software Project Management process for the Entry profile. Given the scarcity of similar studies and the need for reconciling agile-rigorous software development practices, this study contributes to a plausible solution for very small organizations. Finally, further empirical research is encouraged to confirm, update, and extend the results reported in this investigation.